ANALISIS RASIO PROFITABILITAS DAN LIKUIDITAS DALAM MENGUKUR KINERJA KEUANGAN PADA PT CENTRAL INDO PROPERTINDO - Juliana, Juliana; Banjarnahor, Haposan (Aksara Public, 2020)
Thiss research’s intended to analyze the influence of profitabilities ratio (X1) and liquidities ratio (X2) at PT Central Indo Propertindo. In this research, method used quantitative descriptive and financial statement through three variables that two independent variables as Profitability Ratio (X1) and Liquidity Ratio (X2) with one dependent variable as Financial Performance (Y). The population and sample for this research’re income statement and balance sheet of PT Central Indo Propertindo from 2015 to 2018. Based on analysis, t-test show profitability ratio has a positive and significant effect 0n financal perf0rmance with a significant value about 0,015<0,05, so can be concluded Ha’s accepeted and Ho’s rejected. The liquidilty has a positive and significant effect 0n financial performance with a significant value of 0,000<0,05, so can be concluded Ha’s accepted and Ho’s rejected. For the results of the analysis, f-test show that the profitability and liquidity ratios simultaneuosly have a significant effect on the financial performance 0f PT Central Indo Propertindo with a significant value of 0,000<0,05. So concluded that Ha’s accepted and Ho’s rejected, namely the Profitability and Liquidity ratio has an influence of Financial Performance at PT Central Indo Propertindo.